THE IMPORTANCE OF THE SCHWYZ BREED OF CATTLE IN IMMUNOGENESIS AND CELLETION - Kabilov Sokhib Sherovich; Mamatkulov Orifjon Odiljon ogli (Web of Journals Publishing, 2024)
Describes the work and solutions related to determining the immunogenetic characteristics of cattle brought from Switzerland and the possibilities of their use in breeding, which are kept in a number of regions of our repub.
Keywords: Erythrocyte, blood groups, metabolism, productivity, Alatau breed, Caucasian brown breed, antigen.